Evaluasi Penggunaan Sistem Accurate dalam Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan UMKM (Studi Kasus PT Cerita Rasa Kita) - Yulia Istia ningsih; Eva Setiarini Damanik (Universitas Batanghari Jambi, 2023)
This study aims to evaluate the cycle of financial records at PT. Tell us that we are more accurate in preparing financial reports. Evaluation is done by comparing financial records manually and using an application system. Accounting applications in financial reports play an important role and are very helpful in facilitating the company's operational activities. The application system used in UMKM is the Accurate system. Research conducted at this company using a case study method with qualitative methods. The results of this study indicate that using the Accurate system can make it easier for accounting staff to enter financial data in accordance with UMKM financial reporting standards compared to previously using manual